ANALISIS DAMPAK PROGRAM KAWASAN RUMAH PANGAN LESTARI TERHADAP PENGELUARAN KONSUMSI RUMAH TANGGAPADA KELOMPOK WANITA TANI MEE DISTRIK MIMIKA BARU KABUPATEN MIMIKA - Yunir Patadungan (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2019)
This study aims to: (a) find out and analyze the effectiveness of KRPL program implementation in household of KWT Mee members in perintis district, Mimika Baru District in Mimika Regency, and (b) find out and analyze the significance of differences in vegetable consumption expenditure of KWT Mee member household in perintis district Mimika Baru in Mimika Regency before and after implementing the KRPL program.This research method is a descriptive method, namely the procedure of problem abuse that is investigated by describing the state of the subject or object in the research that can be people, institutions, communities and others in the present and the future.Data were collected using interview observation and documentation methods. To answer the first problem formulation of this study, the analytical tool used was effectiveness analysis with the help of simple statistical methods, while to answer the second problem formulation paired t test was used.The analysis shows: (a) the implementation of the KRPL program in KWT Mee member household in perintis village, Mimika Baru District, Mimika Regency has been running effectively, with the achievement value of the effectiveness of the program implementation of 86.77% which is in the very effective category, and (b) there significant difference in consumption of household vegetable consumption from household members of KWT Mee, perintis village, Mimika Baru district, Mimika regency before and after implementing the KRPL program, where the average vegetable consumption expenditure of the program participants after participating in the program is smaller than the average vegetable consumption expenditure community participating in the program before joining the program.